PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS POTENSI LOKAL UNTUK MENINGKATKAN LIVING VALUES PESERTA DIDIK SMA DI KABUPATEN WONOSOBO - Sarah, Siti; -, Maryono (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
Various irregularities among learners such as drugs, fights, and free sex show low values ​​of life (living values) learners. Learning physics that utilize local potentials can be a solution to improve the living values​​, especially high school students in Wonosobo regency. This study was conducted to determine 1) how the development of physics-based learning tools that can improve the local potential values ​​living high school students in Wonosobo regency and 2) how the results/implementation of high school physics learning tools developed in Wonosobo regency.This study design in the form of research and development using the model of Borg & Gall which contains seven steps of research: (1) collecting information, (2) do the design, (3) developing the initial product form, (4) conduct field trials beginning, (5) revise the main product, (6) to test the main field, and (7) revise the main field test. The products will be produced in the form of physics-based device which includes living local potential values ​​for high school students in Wonosobo regency include: syllabi, lesson plans, textbooks, student activity sheet, and assessment sheets.There are two conclusions from the research. 1) The device physics learning developed by utilizing local potential can improve the living values ​​high school students in the district of Wonosobo. 2). There is a significant difference between living values learners who use the local potential of physics-based learning to the learners who learn without using the local potential based learning.